(untitled) (Journal of Analytical Oncology, 2020)
Background: Despite recent therapeutic improvements, the prognosis of unresectable gastric cancer remains poor. Upregulation of programmed cell death ligand 1 (PD-L1) in tumor cells is believed to be an important mechanism to escape from the host immune response. The expression of PD-L1 in tumors is regulated in a highly complex manner by various upstream signaling molecules, depending on the cell type. Given that the efficacy of chemotherapeutic agents for metastatic gastric cancer is limited due to immune escape caused by enhanced PD-L1 expression, PD-1/PD-L1 targeted immunotherapy may be a promising alterative for chemotherapy. However, immune checkpoint inhibitor monotherapy has shown clinical benefits in less than 20% of patients with gastric cancer and its underlying mechanism remains to be elucidated. On the other hand, lentinan, a glucan purified from Shiitake mushrooms, has significant immune-stimulating effects and has been reported to improve survival in patients with metastatic gastric cancer receiving chemotherapy. In the current study we investigated the mechanism by which lentinan increases the chemotherapeutic efficacy by focusing on the expression of PD-L1. Methods: To evaluate the effects of lentinan as well as antineoplastic agents, the expression of PD-L1 and associated molecules was analyzed by real-time polymerase chain reaction and western blotting using the human gastric cancer cell lines, NUGC3, MKN1, and MKN45. Results: Treatment with either cisplatin or oxaliplatin dose-dependently enhanced PD-L1 mRNA and protein expression through the mitogen-activated protein kinase (MAPK) pathway in gastric cancer cells. However, lentinan treatment inhibited the platinum drug-stimulated expression of PD-L1 in gastric cancer cells mainly by suppressing MAPK signaling without affecting the phosphatidylinositol-3 kinase/AKT pathway or transcription factors. Conclusions: Platinum-based drugs enhanced the expression of PD-L1 via the MAPK pathway in gastric cancer cells. Lentinan downregulated PD-L1 expression induced by either cisplatin or oxaliplatin, suggesting that a combination of this glucan and platinum-based chemotherapy could restore the chemosensitivity of cells.